MENGHITUNG MANFAAT EKONOMI PEMBANGUNAN INFRASTRUKTUR TRANSPORTASI - Aleksander Purba (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
Economic growth and available of infrastructures supply are requirement to fulfill demand ofpassengers and goods movement. In other hand, the restrictions of available budget could beobstacle to implement due to city’s limited budget that should financed other sectors such ashealthy, education, running water, garbage etc.City’s of Bandar Lampung try on searching secondary finance as an alternative source throughPusat Investasi Pemerintah (PIP), a special institution of Financial Ministry, reserve fundedconstruction of few project which consist of two flyovers and widening of seven main roads acrossthe city.Off course, it’s rightfully if public and taxpayers want to find out what are the benefit of thoseproject and how substantial would be influence for Bandar Lampung. Does a loan would becommensurable to obtained long term benefit? Research aims to enumerative the economicbenefit of construction of transport infrastructure, that’s as a whole will be fully complete danoperate. Meanwhile the widening section of seven main roads had completely a head. The resultshows that’s economic benefits of these project, direct and indirect, is bigger than wholesaleinvestment.